Effects of a hyperandrogenaemic state on the proliferation and decidualization potential in human endometrial stromal cells - Freis, Alexander; Jauckus, Julia; Strowitzki, Thomas; Germeyer, Ariane (Archives of gynecology and obstetrics, 2017)
ObjectivePolycystic ovary syndrome (PCOS) is the most common endocrine disorder in women, involving hyperandrogenaemia and insulin resistance. Treatment options include dexamethasone, as well as the off-label use of metformin. To evaluate the impact of those drugs on cyclic changes in endometrial development, we tested possible effects of metformin and dexamethasone on endometrial stromal cells decidualisation, proliferation, and gene regulation in a hyperandrogenaemic microenvironment in vitro.Methods/designTen endometrial biopsies (of which five were decidualized in vitro) were used from regularly cycling women. Cells were treated with testosterone, dexamethasone, and metformin in different concentrations. Thereafter, cells were assessed for proliferation and decidualization capacity, as well as mTor and MMP-2 gene regulation.ResultsMetformin showed a dose-dependent negative effect on prolactin secretion, a known decidualization marker. This effect was stronger in a hyperandrogenaemic condition and could not be compensated by dexamethasone. Testosterone had a dose dependent negative effect on proliferation in decidualized endometrial stromal cells. Dexamethasone slightly compensated the negative proliferative effect only in low-dose testosterone. High-dose metformin also showed a dose-dependent reduction in endometrial stromal cell proliferation without a major impact by testosterone or dexamethasone in decidualized and non-decidualized cells. High-dose metformin significantly reduced the expression of matrix metalloproteinase-2 (MMP-2) and mechanistic Target of Rapamycin (mTor), regardless of the concentration of dexamethasone and testosterone. The strongest effect could be observed for the combination with high-dose dexamethasone.ConclusionWhen therapies, such as metformin and dexamethasone, are used to normalize peripheral androgen levels in patients with PCOS, their effect on the endometrial microenvironment should be taken into consideration as well, especially metformin has to be used with caution because of its dose dependent, possibly inhibiting effect at the endometrial proliferation.